Liberal imperialism in Germany : expansionism and nationalism, 1848-1884 - Fitzpatrick, Matthew P. (Monographs in German history, 2008)
In a work based on new archival, press and literary sources, the author revises the picture of German imperialism as being the brainchild of a Machiavellian Bismarck or the "conservative revolutionaries" of the twentieth century. Instead, Fitzpatrick argues for the liberal origins of German imperialism, by demonstrating the links between nationalism and expansionism in a study that surveys the half century of imperialist agitation and activity leading up to the official founding of Germany's colonial empire in 1884.